THE EFFECT OF E-SPORTS VIEWERS’ CUSTOMER EXPERIENCE ON PURCHASE INTENTION - Buffon Ciro Delvecchio; Rayi Retno Dwi Asih (Indonesian Management and Accounting Research, 2026)
This study examines the influence of customer experience on purchase intention toward sponsor brands among e-sports viewers, with social identification as a mediating variable. Customer experience is conceptualized through four dimensions: cognitive, affective, sensory, and social experience. A quantitative survey was conducted with 211 Generation Z respondents who regularly watch e-sports via streaming platforms, and the data were analyzed using Structural Equation Modeling (SEM) with AMOS. The findings show that affective and social experiences significantly enhance social identification, whereas cognitive and sensory experiences do not. Social identification also has a significant positive effect on purchase intention. Indirect effects reveal that affective and social experiences influence purchase intention through social identification, while cognitive and sensory experiences do not exhibit significant mediation. These results underscore the importance of emotional and social engagement in strengthening consumer attachment and purchase intention toward sponsor brands in the e-sports context